Supervisory Support, Organizational Justice and Perceived Organizational Support: A Review and Research Agenda - Onn, Choong Yuen; ., Choe Kum Lung (Information Management and Business Review, 2014)
Past studies have confirmed the relationship between organizational justice and supervisory support with perceived organizational support. However, there is lack of research study conducted on examining the relationship of these two dimensions specifically on the academic staff in Malaysian universities. Furthermore, some researchers also found that organizational support and supervisory support are strongly related to perceived organizational support. Hence, the purpose of this conceptual paper is to provide a review and an examination on the relationship of organizational justice and supervisory support on perceived organizational support among academic staff in Malaysian universities. Conceptual framework and hypotheses have been formulated. The target population is academic staff of Malaysian universities. A simple statistical analysis has been conducted such as reliability analysis and descriptive analysis.